Model Pembelajaran Problem Based Learning (PBL) Meningkatkan Hasil Belajar Matematika Siswa - Mahagia, Febriany A.; Goni, Agnes M.; Rorimpandey, Widdy H. F. (Peneliti.net, 2023)
This research aims to determine the effect of implementing the problem based learning model to improve Mathematics learning outcomes for fifth grade students at GMIM PINARAS Elementary School. This research method uses quantitative methods. The sample in this study consisted of 30 students and used a saturated sampling technique. Data collection techniques use questionnaires and documentation. The instrument used in this research is a questionnaire instrument or questionnaire using a Likert scale. Using data analysis techniques for validity testing and reliability testing for data quantity testing, linearity testing for prerequisite testing and simple linear regression testing for hypothesis testing. The results of the research show that there is a significant influence of the application of the problem based learning model on the mathematics learning outcomes of class V at GMIM Pinaras Elementary School. With a calculated F value = 17,531 and a significance value of 0.001 or less than 0.05